Amphipathic helical peptides hamper protein-protein interactions of the intrinsically disordered chromatin nuclear protein 1 (NUPR1) - Santofimia-Castaño, Patricia; Rizzuti, Bruno; Abián, Olga; Velázquez-Campoy, Adrián; Iovanna, Juan L.; Neira, José L. (Biochimica et biophysica acta. General subjects, 2018)
NUPR1 is a multifunctional intrinsically disordered protein (IDP) involved, among other functions, in chromatin remodelling, and development of pancreatic ductal adenocarcinoma (PDAC). It interacts with several biomolecules through hydrophobic patches around residues Ala33 and Thr68. The drug trifluoperazine (TFP), which hampers PDAC development in xenografted mice, also binds to those regions. Because of the large size of the hot-spot interface of NUPR1, small molecules could not be adequate to modulate its functions. We explored how amphipathic helical-designed peptides were capable of interacting with wild-type NUPR1 and the Thr68Gln mutant, inhibiting the interaction with NUPR1 protein partners. We used in vitro biophysical techniques (fluorescence, circular dichroism (CD), nuclear magnetic resonance (NMR) and isothermal titration calorimetry (ITC)), in silico studies (docking and molecular dynamics (MD)), and in cellulo protein ligation assays (PLAs) to study the interaction. Peptide dissociation constants towards wild-type NUPR1 were ~ 3 μM, whereas no interaction was observed with the Thr68Gln mutant. Peptides interacted with wild-type NUPR1 residues around Ala33 and residues at the C terminus, as shown by NMR. The computational results clarified the main determinants of the interactions, providing a mechanism for the ligand-capture that explains why peptide binding was not observed for Thr68Gln mutant. Finally, the in cellulo assays indicated that two out of four peptides inhibited the interaction of NUPR1 with the C-terminal region of the Polycomb RING protein 1 (C-RING1B). Designed peptides can be used as lead compounds to inhibit NUPR1 interactions. Peptides may be exploited as drugs to target IDPs. [Display omitted] •Amphipathic helical peptides hamper interactions of NUPR1.•Amphipathic helical peptides bind to NUPR1 with low micromolar affinity.•Peptides designed on physical-chemical grounds inhibit protein-protein interactions.•Designed peptides can be used to inhibit interactions of IDPs.